Developing an Appropriate Digital Hearing Aid for Low-Resource Countries: A Case Study - Israsena, P. (Hindawi Publishing Corporation, 2013)
This paper reviews the development process and discusses the key findings which resulted from our multidisciplinary research team's effort to develop an alternative digital hearing suitable for low-resource countries such as Thailand. A cost-effective, fully programmable digital hearing aid, with its specifications benchmarking against WHO's recommendations, was systematically designed, engineered, and tested. Clinically it had undergone a full clinical trial that employed the outcome measurement protocol adopted from the APHAB, the first time implemented in Thai language. Results indicated that using the hearing aid improves user's satisfaction in terms of ease of communication, background noises, and reverberation, with clear benefit after 3 and 6 months, confirming its efficacy. In terms of engineering, the hearing aid also proved to be robust, passing all the designated tests. As the technology has successfully been transferred to a local company for the production phase, we also discuss other challenges that may arise before the device can be introduced into the market.